Introducing the Spatial Conflict Dynamics Indicator of Political Violence - Walther, Olivier J. (Terrorism and political violence, 2023)
While the location of violent events and their propensity to cluster together in space is increasingly well known, a deeper exploration of their spatiality and spatial evolution over time remains an emerging frontier in “Big Data”-driven conflict studies. The new Spatial Conflict Dynamics indicator (SCDi) introduced in this article contributes to fill this gap, by measuring both the intensity and spatial concentration of political violence at the subnational level. Articulating between point pattern and areal spatial analyses, the SCDi allows conflict researchers and analysts to not just map which regions experience the most violence but to track how the geography of conflict evolves over time. The SCDi identifies four spatial typologies of violence and can leverage political event data from most datasets with locational information and can be used for analyses across large multi-state regions, within a single state, or in more localized contexts. In this paper, we illustrate the SCDi with an application to the case of North and West Africa, analyzing over 30,000 discrete events through a twenty-two-year time span and across a twenty-two-state geographical area. We perform a longitudinal analysis of the SCDi typologies to show how the indicator can inform a theory of the spatial lifecycle of violence in the region. The indicator, therefore, has potential as both an analytic tool and a window on conflict episodes, showing how they can change from conflict initiation through resolution.